Passion - Kate, Lauren (New York : Delacorte Press, 2011)
Desperate to unlock the curse that condemns her love for Daniel, Luce revisits her past incarnations trying to understand her fate, but Daniel is chasing her throughout the centuries in order to keep her from rewriting their history.
Sequel to: Torment.
Sequel: Rapture.
Keywords: Paranormal fiction; Reincarnation -- Juvenile fiction; Love -- Fiction; Angels -- Juvenile fiction